KONTAMINASI BAHAN PLASTIK PADA JAJANAN PASAR (GORENGAN) YANG BEREDAR DI KOTA MEDAN - Dita Sari; Riyanto Riyanto; Abdul Karim (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
This reseach aims to know the contamination of plastic materials that exist in market snacks (fried banana, fried tempe, fried tofu and bakwan goreng) that circulated in Medan City. This research uses the method of "Qualitative Description" that is by checking the plastic content in market snacks (gorengan) circulating in Medan City. The results of this study contained 12 positive samples contaminated with plastic materials and 48 samples were not contaminated with plastic materials. Plastic contaminated samples are tested by burning, if positive samples containing plastics will burn and a large flame is visible, black droplets and smell of burning plastic.